Clinical, genomic, and metagenomic characterization of oral tongue squamous cell carcinoma in patients who do not smoke. Issue 11 (23rd August 2014) - Li, Ryan; Faden, Daniel L.; Fakhry, Carole; Langelier, Chaz; Jiao, Yuchen; Wang, Yuxuan; Wilkerson, Matthew D.; Pedamallu, Chandra Sekhar; Old, Matthew; Lang, James; Loyo, Myriam; Ahn, Sun Mi; et al.
Abstract Background Evidence suggests the incidence of oral tongue squamous cell carcinoma is increasing in young patients, many who have no history of tobacco use. Methods We clinically reviewed 89 patients with oral tongue cancer. Exomic sequencing of tumor DNA from 6 nonsmokers was performed and compared to previously sequenced cases. RNA from 20 tumors was evaluated by massively parallel sequencing to search for potentially oncogenic viruses. Results Non‐smokers (53 of 89) were younger than smokers (36 of 89; mean, 50.4 vs 61.9 years; p < .001), and seemed more likely to be women (58.5% vs 38.9%; p = .069). Nonsmokers had fewer TP53 mutations (p = .02) than smokers. No tumor‐associated viruses were detected. Conclusion The young age of nonsmoking patients with oral tongue cancer and fewer TP53 mutations suggest a viral role in this disease. Our efforts to identify such a virus were unsuccessful. Further studies are warranted to elucidate the drivers of carcinogenesis in these patients. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1642–1649, 2015